An Analysis on the Factors Affecting Credit Selection In BPR to Increase Competitiveness - Nobertus Purnomo Lastu; Werner Ria Murhadi; Ratna Widyanti W (Politeknik Ubaya, 2020)
Bank Perkreditan Rakyat (BPR) is a part of the banking financial institutions apart from the commercial banking. .One of the activities of the BPR is to distribute the credits as done by the commercial banks. The problems of BPR as micro financial institutions. In doing their business to distribute the credit up to certain amount, are the commercial banks which have more competitive advantages, in both the price and facilities provided. The objective of this research is to identify the factors influencing the customers in making decisions to take the credit at BPR. By identifying the determinant factors in choosing the banks, BPR can use it to improve their services to the customers and at the same time BPR can use it as a strategy in giving credit to the customers or debtors. The method used in this study was regressive logistic method, which was used to identify what factors determine the customers to choose credist at BPR. The conclusion is that the procedures and personality of the staffs are the main factors making the customers choose credits at BPR.